Recent Developments in Hydrodecyanation and Decyanative Functionalization Reactions. Issue 1 (25th November 2021) - Paul, Nilanjan; Patra, Tuhin; Maiti, Debabrata
Abstract: Nitrile is one of the ubiquitous functional groups in natural products and polymer industry. It is often used as a versatile building block in synthetic chemistry. Classically, nitrile group is used for alpha functionalization, ortho −C−H activation and as a precursor for amine or carbonyl functionalities. With the development of various transition metal catalyzed methods, in the last two decades, nitrile group has emerged as a source of carbon synthons through C−CN bond activation despite of its high bond energy. In this review we have summarized all recent developments involving the carbon synthons arising from the cleavage of C−CN bonds. Depending on the fate of the carbon center after cleavage, all the reactions are classified in two major categories for the ease of discussion: 1) decyanation (removal of the nitrile group) and 2) decyanative functionalization (replacement of the nitrile group). Finally, current limitations in C−CN bond activation strategies and future prospects are discussed. Abstract : A comprehensive overview on different decyanative functionalization strategies is presented. The role of different transition metals and organic electron donors in C−CN bond cleavage and subsequent diversifications is detailed with underlying mechanistic rationale. Finally, a brief outlook on the current limitations along with future directions is outlined.